2018
DOI: 10.5194/acp-2018-922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introduction to Special Issue – In-depth study of air pollution sources and processes within Beijing and its surrounding region (APHH-Beijing)

Abstract: <p><strong>Abstract.</strong> APHH-Beijing (Atmospheric Pollution and Human Health in a Chinese Megacity) is an international collaborative project to examine the emissions, processes and health effects of air pollution in Beijing. The four research themes of APHH-China are: (1) sources and emissions of urban atmospheric pollution; (2) processes affecting urban atmospheric pollution; (3) exposure science and impacts on health; and (4) interventions and solutions to red… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 22 publications
(23 reference statements)
0
35
0
Order By: Relevance
“…2.1. The regional transport defined by Sun et al (2014) was LTC + RLC + RTC, whereas in the studies by J. and Timmermans et al (2017), it was RLC + RTC. In this study, we employed RLC + RTC as regional transport.…”
Section: The Impact Of Regional Transport Of Sulfate and Its Precursomentioning
confidence: 91%
See 3 more Smart Citations
“…2.1. The regional transport defined by Sun et al (2014) was LTC + RLC + RTC, whereas in the studies by J. and Timmermans et al (2017), it was RLC + RTC. In this study, we employed RLC + RTC as regional transport.…”
Section: The Impact Of Regional Transport Of Sulfate and Its Precursomentioning
confidence: 91%
“…These formed sulfates may have been blown back to Beijing under specific weather conditions and were previously considered regional transport. The contribution of LTC also largely explains the difference in estimated regional transport contributions between Sun et al (2014) and J. . In the present study, LTC + RLC + RTC accounted for 58 %-70 % of the sulfate concentration in the six episodes, which is relatively similar to the estimation (75 %) of Sun et al (2014), which was based on the observed hourly increase rate of the local sulfate concentration.…”
Section: The Impact Of Regional Transport Of Sulfate and Its Precursomentioning
confidence: 96%
See 2 more Smart Citations
“…To the knowledge of the authors, this is the first time these emissions have been directly quantified in Beijing. This work was carried out as part of the Air Pollution and Human Health (APHH) Beijing project and an overview of this campaign can be found in Shi et al (2019). Instrumentation was housed in a temporary shipping container laboratory located at the base of the tower.…”
mentioning
confidence: 99%